A productivity dashboard for hospitals: An empirical study - Pestana, Miguel Ricardo Cardoso Morais (2018)
Health units are institutions which require accurate, updated information to support managerial decisions for thriving in such a critical industry. Thus, health information systems have been developed to help hospital managers steer daily operations. These systems provide not only operational support, but also key performance indicators (KPI’s) to monitor relevant areas at a time-aggregated basis. Despite the recognized value of dashboards in helping decision-makers, the literature shows a lack of proposals of productivity dashboards to assist Hospitals stakeholders. The thesis focuses on two problems: Hospital organizations need access to production and productivity information to improve access to services. Managers need production and productivity information to optimize resource allocation. The importance of addressing these issues lies in the fact that to monitor production and productivity information, is it possible to improve resource allocation. This dissertation consists of the development of dashboards to monitor information obtained from a hospital organization at the level of production and productivity, with the mission of supporting decision makers in the decision process. To properly develop the productivity dashboard, the Design Science Research (DSR) methodology was adopted to build and evaluate the artefact. It was ascertained that the production and productivity segment need more study and that the dashboards on these themes is an asset at the level of monitoring and analysis and subsequent decision-making process. The expected contribution of this research is to develop a dashboard recognized by health stakeholders as capable of better assisting them during their management duties.